Characterization and impact of planthopper (Sanurus indecora) infestation on kepel (Stelechocarpus burahol) plants - Saputra, Yudha; Anindita, Devina Cinantya; Hadiyanti, Nugraheni; Supandji, Supandji; Hapsari, Lia (Universitas Lancang Kuning, 2024)
Kepel (Stelechocarpus burahol), designated as the floral identity of the Special Region of Yogyakarta, Indonesia, faces challenges from plant pests that threaten its sustainability. Understanding the morphology and impact of pests such as planthoppers on kepel is crucial for developing effective pest management strategies. Despite its significance, there is a gap in research regarding the specific pests affecting kepel and their impact. This study aims to identify the morphological characteristics of planthopper pests and examine their infestation levels on kepel plants. Using a qualitative method with purposive sampling, samples were collected from kepel plants identified as infected by tree planthoppers. Morphological observations identified the pest species as Sanurus indecora from the Flatidae family. Sampling from two infected plants resulted in 81 nymphs and 16 adult S. indecora. Infestation analysis showed that kepel plant XII.G.D had a 7.4% infestation rate, while XIV.G.II had a 23% infestation rate. These findings highlight the presence and impact of S. indecora on kepel plants, providing critical information for the bioecology of this pest. This study not only fills a research gap by documenting the pests affecting kepel but also contributes to the broader knowledge required for developing targeted pest management strategies, ensuring the conservation and health of kepel plants in Yogyakarta, Indonesia.